Effect of Substrate Materials on Diamond Deposition Synthesized by Microwave Plasma CVD Process - KO, Ensei; HOSOMI, Satoru; YOSHIDA, Isao; CHEN, Chia-Fu (Hyōmen gijutsu, 1990)
Diamond deposition by a microwave plasma CVD process was observed using substrates of different chemical natures. The reaction gas consisted of CH4 and H2, with the latter supplied at a rate of 100cm3/min, while a pressure of 2.3kPa was maintained in the chamber. The CH4 concentration was set generally at 0.6vol%; the microwave output was at 120W. Diamond formed at high densities on substrates of W, Mo, Ta or Zr, so these materials, pre-scratched, are suitable for a diamond film deposition. In contrast, the deposition occurred at much lower densities on Au, Pt, Cu or Pd, which thus seemed more suitable for a growth of particles. No diamond formed on any of the ferrous metals studied, but the materials, when coated with ceramics, served as good substrates. Cobalt had to be removed from the surface of the cemented carbide or sintered diamond before they could serve well as substrates. By depositing diamond on the mixture particle of amorphous carbon and diamond, it was possible to produce particles which had numerous small edges on the surface and which may find applications as an abrasive material.